PENGARUH KARAKTERISTIK INDIVIDU DAN ETOS KERJA TERHADAP KOMITMEN ORGANISASIONAL SERTA IMPLIKASINYA PADA KINERJA PEGAWAI (Studi pada Puskesmas Singosari Kabupaten Malang) - Nur Rasuna Intan; Rahayu Puji Suci; Dharmayanti PH (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to obtain empirical evidence about the influence of individual characteristics and work ethic on employee performance, both directly and through the mediation of organizational commitment. This type of research is quantitative with the SEM-SmartPLS method. Data was obtained through a questionnaire distributed to 44 employees of the Singosari Community Health Center, Malang Regency. The sample is determined by census or saturated sample. Empirical evidence shows that individual characteristics and work ethic have a significant effect on organizational commitment, but on employee performance, individual characteristics do not have a significant effect. The mediating role of organizational commitment is significant, both for the influence of individual characteristics on employee performance and the influence of work ethic on the performance of employees at the Singosari Health Center, Malang Regency